Analisis Sistem Antrian Pengujian Material Pada Laboratorium Pengujian Konstruksi Dengan Metode Queuing Theory Menggunakan Software POM QM - Roesmita S. Alam; Moch. Tutuk Safirin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
A construction testing laboratory is a special facility used to carry out various types of testing and analysis of construction materials, structures and construction components. It is always busy with customers, so sometimes there are huge queues of customers. Thus, research was conducted to determine the effectiveness of the construction testing laboratory queuing system. The method used in this research is Queuing Theory. Queuing Theory is a theory related to mathematical studies and queues or waiting lines. Queuing theory is always related to all aspects of the customer's situation in obtaining a service. Analysis of material testing queues in construction laboratories using the M/M/S model shows increased efficiency after adding servers. Previously, the server usability rate was 50%, with a queue time of 0.5%. After adding servers, the usability rate increases to 75%, queue time decreases, and the probability of customers being served increases to 2.11%. These results are the basis for recommendations for improvements to increase efficiency and customer satisfaction .